The impact of interwoven integration practices on supply chain value addition and firm performance - Shashi; Madjid Tavana; Amir Shabani; Rajwinder Singh (Journal of Industrial Engineering International, 2019)
Drawing on the supply chain (SC) management literature, this article conceptualizes and empirically tests a framework that shows how both external and internal integration practices are significant and positively associated with SC value addition and firm performance. The framework also tests the impact of value addition as a reinforcing factor on firm performance. The outcome of this investigation is interesting for both SC researchers and practitioners because the current SC integration literature is conflicting. A structural equation modeling technique, using a sample of 366 large-scale manufacturing companies based in India, is considered in this paper to test the framework. The results support all five research hypotheses which indicate that paramount firm performance requires tight external and internal integration and higher level of value addition. Although the external integration is found to be rather influential than the internal integration, SC players need to have integrated internal business processes for tight external integration. This paper also explains the implication of collective planning and decision making to respond promptly to external market events and reveals the importance of value addition.
Keywords: 650; Supply chain management; Planning; Integration; Value addition; Firm performance